The Implementation of Final Examination and Teaching and Learning - UMP, PNC (2020)
1. The Covid-19 pandemic has engulfed and impacted the world including the UMP community. Thus, it is necessary for the UMP management to make decisions based on the latest development of the pandemic to ensure its academic activities meet the learning outcomes and the high standard quality.